2D interactions and binary crystals of dipolar and quadrupolar nematic colloids. - Ognysta, U; Nych, A; Nazarenko, V; Musevic, I; Skarabot, M; Ravnik, M; Zumer, S; Poberaj, I; Babic, D (2008)
In this Letter, we demonstrate that the symmetry of the elastic interaction between the dipolar and quadrupolar colloidal particles in the nematic liquid crystal leads to a novel variety of 2D nematic "binary" colloidal crystals, which have not been observed in any colloidal system. The dipolar-quadrupolar interaction is highly anisotropic and shows a power-law dependence when the particles approach each other along the director field with a pair-binding energy of the order of several thousands of k(B)T for 4 microm diameter colloids.